Enhancing Savonius Turbine Self-starting Capability by Installing a Circular Cylinder in Front of Returning Turbine Blade - Tri Yogi YUWONO; Ramadhan Ananto Bagas; Paramesti Suksmatatya; Merbasari Mahardina Festy; Lisdarina Elza; Nabila Arif Vega; Jeremia Dionisius; Lawrence Budhiarto Michael; Shuhufam Afiyah (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2021)
The effect of installing a circular cylinder in front of the returning turbine blade in enhancing the self-starting capability of the Savonius wind turbine has been studied experimentally by measuring the static torque of the turbine at the angular positions of the blades. The circular cylinder with a diameter relative to the blade diameter d/D = 0.5 is installed at a distance corresponding to the blade diameter in front of the returning turbine blade which is varied by 1.2 ≤ S/D ≤ 2.6. The experiments were carried out for Reynolds number (Re) = 74,000, 136,000, and 175,000. The results showed that the presence of a circular cylinder installed in front of the returning turbine blade at a distance of 1.4 ≤ S/D ≤ 1.8 was able to achieve the self-starting capability of the Savonius wind turbine as indicated by the positive values of the turbine static torque coefficient at all blade angular positions. The highest performance of the Savonius turbine self-starting capability is obtained at the circular cylinder position S/D = 1.6 for the Reynolds number (Re) = 136,000, and 175,000.